Variabel – Variabel Penentu Terjadinya Kecurangan ( Froud ) ( Studi Pada Dinas Pekerjaaan Umum Dan Penataan Ruang Kota Malang ) - Sukariyono, Dedi (Arthavidya Jurnal Ilmiah Ekonomi, 2018)
Cheating or fraud are unlawful acts committedintentionally for a particular purpose (manipulation ormisrepresentation of another party) done by persons from withinor outside the organization for personal or group gain directlyor indirectly other parties. Many of the fraud determinants,including internal control systems, information asymmetry, lawenforcement, organizational commitment.In this regard, thepurpose of this study is to analyze which of the variables XIinternal control system, information asymmetry X2, X3 lawenforcement, and organizational commitment X4, as adeterminant of fraud on the Department of Public Works andSpatial Planning (DPU & PR) ) Malang city This research wasconducted in the Office of DPU & PR Malang. A sample of 102Civil Servants was taken randomly. Data were collected throughquestionnaires given directly to respondents. Analysis techniqueusing factor analysis. Prior to the analysis, first tested thevalidity and reliability. The result of this research proves thatthe determinant of fraud occurrence in Public Works andSpatial Planning (DPU & PR) Malang City is, first there isinformation asymmetry (existence of unbalanced information)between party of DPU & PR with stakeholders. Where the DPU& PR have more and better information about the activities itdoes than the stakeholders. The main indicator as a determinantof the variable asymmetry of information is that "only theinternal agency that knows all the information related to thetransaction financial statements". Secondly, there is inconsistentlaw enforcement in the handling of regulatory violations. Themain indicator as a determinant of law enforcement variables isthat "in DPU & PR, officials are inconsistent in handlingregulatory violations".Keywords: internal control system, information asymmetry, lawenforcement, organizational commitment, cheating